2014
DOI: 10.1002/iroh.201301640
|View full text |Cite
|
Sign up to set email alerts
|

TranslocatedEsox luciusL. (PISCES) trigger aTriaenophorus crassusForel (CESTODA) epidemic in a population ofSalvelinus umbla(L.) (PISCES)

Abstract: In 2005, an epidemic of the pike tapeworm Triaenophorus crassus Forel, 1868 broke out in the Arctic charr (Salvelinus umbla (L. 1758)) stock of Lake Grundlsee, Austria. Besides the definitive host Northern pike (Esox lucius L. 1758), which was introduced into the lake in the 1960s, the cestode requires copepods as first and salmonid fish as second intermediate hosts. Within 2 years, the prevalence of the cestode in medium sized Arctic charr increased to almost 100% and the abundance reached a maximum of 55 cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…Although all C. lavaretus and ~16% of S. umbla investigated in Lake Achensee were infested with T. crassus (Schähle et al, 2014), the prevalence of the parasites was low (0.38%; maximum infection rate, 3.7%; Fig. 2), but comparable to studies from several lakes in Austria (Lahnsteiner et al, 2009;Sichrowsky et al, 2013;Schaufler et al, 2014), France (Hanzelova and Gerdeaux, 2003) or Canada (Watson and Lawler, 1965). In Lake Fuschlsee, for example, up to ~2% (mean 0.4%) of the C. abyssorum population were infested with Triaenophorus procercoids (Sichrowsky et al, 2013).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Although all C. lavaretus and ~16% of S. umbla investigated in Lake Achensee were infested with T. crassus (Schähle et al, 2014), the prevalence of the parasites was low (0.38%; maximum infection rate, 3.7%; Fig. 2), but comparable to studies from several lakes in Austria (Lahnsteiner et al, 2009;Sichrowsky et al, 2013;Schaufler et al, 2014), France (Hanzelova and Gerdeaux, 2003) or Canada (Watson and Lawler, 1965). In Lake Fuschlsee, for example, up to ~2% (mean 0.4%) of the C. abyssorum population were infested with Triaenophorus procercoids (Sichrowsky et al, 2013).…”
Section: Discussionsupporting
confidence: 67%
“…2). This is relatively late in the year compared to the first procercoid occurrence in other Austrian lakes (from mid-May to beginning of June; Lahnsteiner et al, 2009;Sichrowsky et al, 2013;Schaufler et al, 2014), but corresponds with the lower water temperature found in our study system. In Lake Achensee, highest infection rates of Triaenophorus spp.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The costs for the 54 gill nets (70.0 EUR n −1 ), 54 fykes (190.0 EUR n −1 ) and the harpoon (100.0 EUR) bought for this study were divided by the respective numbers and weights of pike caught. Infection rates of T. crassus in Arctic charr were monitored concurrently to assess the impact of intensive pike removal (see Schaufler et al, ).…”
Section: Methodsmentioning
confidence: 99%